1998
DOI: 10.1590/s1516-89131998000300010
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Candida guilliermondii FTI 20037 on mixed substrate

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…The major differences in the overall growth rate between wild type and XDH1 defective strains can most probably be attributed to differences in the ability to utilize xylose. However, the parental strain also grew faster than xdhΔ and xdh∆::XR within the first 24-32 h. In this early growth phase only glucose is supposed to be used (shown by (Gurgel et al 1998) and observed by us, data not shown). This might indicate that an intact xylose metabolic pathway seems to be required for realization of the full growth potential.…”
Section: Discussionmentioning
confidence: 76%
“…The major differences in the overall growth rate between wild type and XDH1 defective strains can most probably be attributed to differences in the ability to utilize xylose. However, the parental strain also grew faster than xdhΔ and xdh∆::XR within the first 24-32 h. In this early growth phase only glucose is supposed to be used (shown by (Gurgel et al 1998) and observed by us, data not shown). This might indicate that an intact xylose metabolic pathway seems to be required for realization of the full growth potential.…”
Section: Discussionmentioning
confidence: 76%